Methodological and dynamical perspective to determine critical moments on sport game - Ferreira, A.P.; Volossovitch, A.; Gonçalves, I. (International Journal of Computer Science in Sport, 2002)
Sport games are characterized by coopération-opposition nature (Moreno, 1989). This reality gives to the sport competition a non-linearity essence that can be observed when two teams are performing their cooperation and opposition tasks during the game. One game has its own history and its course could be completely different from each other but with a similar final result. McGarry et al. (2002) compare the sport competition with a dynamical system, where small and singular events can introduce high alterations on normal organization of whole parts that are playing. Hughes et al. (1998) designated as a "critical incident" any type of alterations in rhythmic flow of a match. Nevertheless, it is possible to define not only critical incidents, but also periods of a match, where the events provoke some instability in the equilibrium of contest. In the case of Basketball, Knight and Newell (1989) named these moments as "critical moments of game". The main goal of this paper is to discuss the new criteria that allow us to identify the critical moments of a sport game, considering the game as a dynamic and open system.